Estudo analise e exemplo de aplicação de geração eólica - Murayama, Roberto Hiroyuki [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Brazil economic growth has to predict the need for implementation of new energy sources to ensure the continuity of the economic growth and improvement of life of the brazilian population. Until this moment, this assistance included the construction of large hydroelectric plants, mainly in the amazon region, where the environmental impact is difficult or, as in the case of the Belo Monte made this impossible so far, the implementation of these projects. In this work is conducted a study that demonstrates an example of application of wind energy, through an assessment of wind resources in the brazilian Northeast for the implementation of a wind farm
Keywords: Energia eólica; Recursos energeticos